Small‐angle X‐ray scattering tensor tomography: model of the three‐dimensional reciprocal‐space map, reconstruction algorithm and angular sampling requirements. Issue 1 (7th December 2017) - Liebi, Marianne; Georgiadis, Marios; Kohlbrecher, Joachim; Holler, Mirko; Raabe, Jörg; Usov, Ivan; Menzel, Andreas; Schneider, Philipp; Bunk, Oliver; Guizar-Sicairos, Manuel
Abstract : The mathematical framework and reconstruction algorithm for small‐angle scattering tensor tomography are introduced in detail, as well as strategies which help to reduce the amount of data and therewith the measurement time required. Experimental validation is provided for the application to trabecular bone. Abstract : Small‐angle X‐ray scattering tensor tomography, which allows reconstruction of the local three‐dimensional reciprocal‐space map within a three‐dimensional sample as introduced by Liebi et al. [ Nature (2015), 527, 349–352], is described in more detail with regard to the mathematical framework and the optimization algorithm. For the case of trabecular bone samples from vertebrae it is shown that the model of the three‐dimensional reciprocal‐space map using spherical harmonics can adequately describe the measured data. The method enables the determination of nanostructure orientation and degree of orientation as demonstrated previously in a single momentum transfer q range. This article presents a reconstruction of the complete reciprocal‐space map for the case of bone over extended ranges of q . In addition, it is shown that uniform angular sampling and advanced regularization strategies help to reduce the amount of data required.